Bioengineering of virus-like particles as dynamic nanocarriers for in vivo delivery and targeting to solid tumours - Mohamed Suffian, Izzat Fahimuddin; Al-Jamal, Khuloud T. (Elsevier, 2021)
Virus-like particles (VLPs) are known as self-assembled, non-replicative and non-infectious protein particles, which imitate the formation and structure of original wild type viruses, however, lack the viral genome and/or their fragments. The capacity of VLPs to encompass small molecules like nucleic acids and others has made them as novel vessels of nanocarriers for drug delivery applications. In addition, VLPs surface have the capacity to achieve variation of the surface display via several modification strategies including genetic modification, chemical modification, and non-covalent modification. Among the VLPs nanocarriers, Hepatitis B virus core (HBc) particles have been the most encouraging candidate. HBc particles are hollow nanoparticles in the range of 30–34 nm in diameter and 7 nm thick envelopes, consisting of 180 or 240 copies of identical polypeptide monomer. They also employ a distinctive position among the VLPs carriers due to the high-level synthesis, which serves as a strong protective capsid shell and efficient self-assembly properties. This review highlights on the bioengineering of HBc particles as dynamic nanocarriers for in vivo delivery and specific targeting to solid tumours.